Germacrene A synthase in yarrow (Achillea millefolium) is an enzyme with mixed substrate specificity: gene cloning, functional characterization and expression analysis - Pazouki, Leila; Memari, Hamid R.; Kännaste, Astrid; Bichele, Rudolf; Niinemets, Ülo (Frontiers in Plant Science, 2015)
Terpenoid synthases constitute a highly diverse gene family producing a wide range of cyclic and acyclic molecules consisting of isoprene (C5) residues. Often a single terpene synthase produces a spectrum of molecules of given chain length, but some terpene synthases can use multiple substrates, producing products of different chain length. Only a few such enzymes has been characterized, but the capacity for multiple-substrate use can be more widespread than previously thought. Here we focused on germacrene A synthase (GAS) that is a key cytosolic enzyme in the sesquiterpene lactone biosynthesis pathway in the important medicinal plant Achillea millefolium (AmGAS). The full length encoding gene was heterologously expressed in Escherichia coli BL21 (DE3), functionally characterized, and its in vivo expression was analyzed. The recombinant protein catalyzed formation of germacrene A with the C15 substrate farnesyl diphosphate (FDP), while acyclic monoterpenes were formed with the C10 substrate geranyl diphosphate (GDP) and cyclic monoterpenes with the C10 substrate neryl diphosphate (NDP). Although monoterpene synthesis has been assumed to be confined exclusively to plastids, AmGAS can potentially synthesize monoterpenes in cytosol when GDP or NDP become available. AmGAS enzyme had high homology with GAS sequences from other Asteraceae species, suggesting that multi-substrate use can be more widespread among germacrene A synthases than previously thought. Expression studies indicated that AmGAS was expressed in both autotrophic and heterotrophic plant compartments with the highest expression levels in leaves and flowers. To our knowledge, this is the first report on the cloning and characterization of germacrene A synthase coding gene in A. millefolium, and multi-substrate use of GAS enzymes.